CONSUMER GRIEVANCE - Ms. Muthumalathi; V. Vinija; A. Surya (Galaxy International Interdisciplinary Research Journal, 2022)
In this project consumer grievance developed for customizing the query and feedback activities with our tight schedule. There will be a five departments under the customer grievance. They are, Electricity board, Electricity problems, Transport, Bus late, Water, Water leakage problems, Public work Department, Road works, Corporation, Garbage Can. The number of users of internet has grown so rapidly that it has become a necessary part of our daily life. Those complaints are posted by the public and viewed by admin and certain employees. The employees does not carry the problems of public. The particular employee can take actions to recover the problems. This is useful for the public to post the query and feedback.